Advances in molecular diagnostics of Neisseria gonorrhoeae - Yu, Choo Yee; Lim, Xin Rui; Van Phan, Thanh; Mat Isa, Nurulfiza; Yean, Chan Yean; Chan, Kok Gan; Ang, Geik Yong (Elsevier B.V., 2025)
Neisseria gonorrhoeae is a human obligate pathogen that causes the sexually transmitted infection (STI) gonorrhea. As the second most commonly reported STI of bacterial origin, gonorrhea is a growing global public health concern given that the causative pathogen has developed resistance to antibiotics that are currently used for treatment. A holistic approach is thus essential to reduce the incidence of gonorrhea and to control the spread of antimicrobial resistance N. gonorrhoeae. Improvement in diagnostics is one of the avenues to combat rising STI rates and this review aims to provide an overview of the strategies used for N. gonorrhoeae nucleic acid detection by examining nucleic acid amplification tests (NAATs) that are cleared by the United States Food and Drug Administration (FDA). The updated and comprehensive information of FDA-cleared NAATs presented in this review includes the recent clearance of NAATs for point-of-care testing and home-based specimen collection kit for gonorrhea testing that can potentially revolutionize STI services. Further progress in the molecular diagnostics for gonorrhea is anticipated along with vaccine development as the challenge remains to meet the World Health Organization goal of reducing the incidence of N. gonorrhoeae infection by 90 % by 2030.